Identification of new enterosynes using prebiotics: roles of bioactive lipids and mu-opioid receptor signalling in humans and mice. Issue 6 (5th October 2020) - Abot, Anne; Wemelle, Eve; Laurens, Claire; Paquot, Adrien; Pomie, Nicolas; Carper, Deborah; Bessac, Arnaud; Mas Orea, Xavier; Fremez, Christophe; Fontanie, Maxime; Lucas, Alexandre; Lesage, Jean; et al.
Abstract : Objective: The enteric nervous system (ENS) plays a key role in controlling the gut-brain axis under normal and pathological conditions, such as type 2 diabetes. The discovery of intestinal actors, such as enterosynes, able to modulate the ENS-induced duodenal contraction is considered an innovative approach. Among all the intestinal factors, the understanding of the role of gut microbes in controlling glycaemia is still developed. We studied whether the modulation of gut microbiota by prebiotics could permit the identification of novel enterosynes. Design: We measured the effects of prebiotics on the production of bioactive lipids in the intestine and tested the identified lipid on ENS-induced contraction and glucose metabolism. Then, we studied the signalling pathways involved and compared the results obtained in mice to human. Results: We found that modulating the gut microbiota with prebiotics modifies the actions of enteric neurons, thereby controlling duodenal contraction and subsequently attenuating hyperglycaemia in diabetic mice. We discovered that the signalling pathway involved in these effects depends on the synthesis of a bioactive lipid 12-hydroxyeicosatetraenoic acid (12-HETE) and the presence of mu-opioid receptors (MOR) on enteric neurons. Using pharmacological approaches, we demonstrated the key role of the MOR receptors and proliferator-activated receptor γ for the effects of 12-HETE. These findings are supported by human data showing a decreased expression of the proenkephalin and MOR messanger RNAs in the duodenum of patients with diabetic. Conclusions: Using a prebiotic approach, we identified enkephalin and 12-HETE as new enterosynes with potential real beneficial and safety impact in diabetic human.